A study on otorhinolaryngological manifestations in pregnant women - Jamwal, Shallu; Kalsotra, Gopika; Manhas, Monica; Raina, Apurva; Kalsotra, Parmod; Ul Islam, Owais; ., Youshita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Pregnancy is characterized by various endocrinological and physiological changes affecting different organs including ear, nose and throat. Otorhinolaryngological manifestations in pregnant women are mainly due to changes in levels of sex hormones such as estrogen and progesterone. While majority of these conditions are benign and reverse after parturition, some do not. The study was conducted with an objective to find the incidence of various otorhinolaryngological manifestations among pregnant women and to create awareness among the medical professionals to diagnose these conditions. Methods: This is a hospital based cross sectional study of 240 pregnant women who presented to the department of otorhinolaryngology with ENT symptoms. Detailed history, general physical examination and complete ENT examination was done on all subjects. Results: 47.9% of the study cases had otological manifestations among which otitis media was the main finding. 16.7 % of the cases had nasal symptoms among which rhinits was the main condition predominantly observed in the 3rd trimester. 19.6% of the cases had oral cavity lesions with stomatitis being the most commonly found cause. 15.8% of the cases had throat complaints, among which gastroesophageal reflux disease (GERD) was the most common cause found during 2nd and 3rd trimester. Conclusions: Recognition and understanding of pregnancy related ear, nose throat complaints will allow otolaryngologist to reassure and manage these patients, improving their experience of the gestational period.